2014
DOI: 10.1113/jphysiol.2014.284125
|View full text |Cite
|
Sign up to set email alerts
|

Virtual leak channels modulate firing dynamics and synaptic integration in rat sympathetic neurons: implications for ganglionic transmission in vivo

Abstract: Key pointsr The synaptic organization of paravertebral sympathetic ganglia enables them to relay activity from the spinal cord to the periphery and thereby control autonomic functions, including blood pressure and body temperature.r The present experiments were done to reconcile conflicting observations in tissue culture, intact isolated ganglia and living animals. By recording intracellularly from dissociated neurons and intact ganglia, we found that when electrode damage makes cells leaky it could profoundly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 64 publications
4
49
0
Order By: Relevance
“…The most salient of these properties was the increase of the probability of firing 2 or more spikes. As shown in Figure 3A and also previously documented (Suzuki and Rogawski 1989; Tompkins et al 2013), MPG neurons can spike once or many times, a phenomena observed in many other autonomic neuron types (Cassell et al 1986; Malin and Nerbonne 2001; Springer et al 2015). One obvious possible mechanism for generating multiple spikes is the activation of a depolarizing current with somewhat slower kinetics that can maintain depolarization above threshold to allow for the generation of multiple spikes.…”
Section: Discussionsupporting
confidence: 83%
“…The most salient of these properties was the increase of the probability of firing 2 or more spikes. As shown in Figure 3A and also previously documented (Suzuki and Rogawski 1989; Tompkins et al 2013), MPG neurons can spike once or many times, a phenomena observed in many other autonomic neuron types (Cassell et al 1986; Malin and Nerbonne 2001; Springer et al 2015). One obvious possible mechanism for generating multiple spikes is the activation of a depolarizing current with somewhat slower kinetics that can maintain depolarization above threshold to allow for the generation of multiple spikes.…”
Section: Discussionsupporting
confidence: 83%
“…The ganglia are proposed to exhibit the ability to amplify the preganglionic signal by distributing axons that produce suprathreshold (i.e., "strong") excitatory postsynaptic potentials from one preganglionic to multiple (e.g., 2-15) postganglionic neurons (Bahr et al 1986;Jänig and Häbler 2000;McLachlan 2003;Purves et al 1986;Wang et al 1995). Furthermore, computational and advanced dynamic clamping methods (Horn and Kullmann 2007;Rimmer and Horn 2010;Springer et al 2015) suggest the ability to enhance the firing probabilities of any postganglionic neuron through convergent synapses from multiple preganglionic neurons that individually produce subthreshold excitatory postsynaptic potentials but, depending on their timing, could summate to cause a postganglionic discharge. How these concepts apply to different ganglia or postganglionic axons of varying size and/or varying targets, or in human ganglia, remain to be studied.…”
Section: The Validity and Reliability Of Postganglionic Sna To Reflecmentioning
confidence: 99%
“…Also, patterns of pre‐to‐post ganglionic convergent innervation have been observed in rodent and amphibian models (Rimmer & Horn, ; Springer et al . ). As the degree of convergence appears to scale with neuron size in mammals (Purves & Lichtman, ; Purves et al .…”
Section: Introductionmentioning
confidence: 97%